Can creative role models prime creativity in soccer players? - Furley, P.; Memmert, D. (Psychology of Sport and Exercise, 2018)
Objectives The goal of the present study was to test if priming soccer players with certain players that are known for extraordinary creativity can lead to enhanced creativity in a computer-based decision-making task. Design Between-subject experimental designs were implemented. Method Using a sequential priming procedure amateur soccer players were primed with either creative (Lionel Messi; Thiago Alcántara) or uncreative soccer players (Per Mertesacker; John Terry) and subsequently performed a soccer decision-making task. The priming stimuli were changed from Experiment 1 ( N =60) to Experiment 2 ( N =60), and the priming procedure was changed in Experiment 3 ( N =60). Results All three experiments revealed large ( d =0.91 in Experiment 1 and d =1.75 in Experiment 2) to moderate effects (Experiment 3; d =0.59) of priming on creative decision making in soccer. Conclusion Domain-specific creative thinking can be influenced by priming amateur soccer players with soccer stars that are known to differ in terms of creativity. Both the practical implications of the findings for soccer and the methodological implications for future priming research in sport are critically discussed.